Penegakan Hukum Oleh Polri Terhadap Pelaku Tindak Pidana Pencurian Sepeda Motor Dengan Pemberatan (Studi di Polrestabes Medan) - Jaya Syah Putra; Rizkan Zulyadi; M.Citra Ramadhan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The purpose of this study was to analyze law enforcement efforts, obstacles and prevention of criminal acts of theft by POLRI against perpetrators of the crime of motorcycle theft with weights in the jurisdiction of Medan Police. This type of research is directed to normative juridical law research. The nature of the research is descriptive analysis of the law enforcement by the Indonesian National Police against the perpetrators of the crime of theft. The results showed that law enforcement efforts were carried out, after the personnel received a complaint report from the victim regarding the occurrence of theft with weighting proceed to the stage of investigation and investigation, against the perpetrators of theft with the weight of a motorcycle subject to Article 363 of the Criminal Code with a maximum penalty of 9 years imprisonment depending on the the method used by the perpetrator to commit theft by weight. Barrier factors include the identity of the perpetrator is not clear, the perpetrator does not have an ID card, the perpetrator does not admit his actions, there are no witnesses at the crime scene. The perpetrator lost evidence, the victim did not want to report it to the police, there were no supporting witnesses. Countermeasures include carrying out preventive measures by carrying out patrols in suspected places, conducting socialization and community approaches in order to create synergistic coordination and cooperation in creating security. Repressive efforts by increasing efforts to take action against perpetrators of theft by weighting motorbikes by providing strict sanctions and having a deterrent effect on perpetrators and providing guidance to the community to comply with the law.